Enantiomeric 4‐Acylamino‐6‐alkyloxy‐2 Alkylthiopyrimidines As Potential A3 Adenosine Receptor Antagonists: HPLC Chiral Resolution and Absolute Configuration Assignment by a Full Set of Chiroptical Spectroscopy. Issue 5 (20th April 2016) - Rossi, Daniela; Nasti, Rita; Marra, Annamaria; Meneghini, Silvia; Mazzeo, Giuseppe; Longhi, Giovanna; Memo, Maurizio; Cosimelli, Barbara; Greco, Giovanni; Novellino, Ettore; Da Settimo, Federico; Martini, Claudia; et al.
Abstract: The chiral separation of enantiomeric couples of three potential A3 adenosine receptor antagonists: ( R/S )‐N‐(6‐(1‐phenylethoxy)‐2‐(propylthio)pyrimidin‐4‐yl)acetamide (1 ), ( R/S )‐N‐(2‐(1‐phenylethylthio)‐6‐propoxypyrimidin‐4‐yl)acetamide (2 ), and ( R/S )‐N‐(2‐(benzylthio)‐6‐sec‐butoxypyrimidin‐4‐yl)acetamide (3 ) was achieved by high‐performanceliquid chromatography (HPLC). Three types of chiroptical spectroscopies, namely, optical rotatory dispersion (ORD), electronic circular dichroism (ECD), and vibrational circular dichroism (VCD), were applied to enantiomeric compounds. Through comparison with Density Functional Theory (DFT) calculations, encompassing extensive conformational analysis, full assignment of the absolute configuration (AC) for the three sets of compounds was obtained. Chirality 28:434–440, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :